Fatores de risco e de proteção presentes no cotidiano de adolescentes moradores do bairro Comandante Gika, Subzona E - Cabinda/ Angola: família, escola e relações comunitárias - Gracietta Francisco Teodora Gime (2014)
The present survey studied risk and protective factors present in the lives of two teenagers dwelling in the Comandante Gika neighborhood, Subdivision E - Cabinda/Angola -, focusing on the adolescents relationship with the school. We investigated the experiences resulting from being a teenager in a context of social risk, taking into account that the Comandante Gika district - Subdivision E is considered as an area of great vulnerability, a community arked by substandard housing, unemployment and lack of electricity, piped drinking water and basic sanitation, among others. Experiences resulting from being teenagers are here understood as the adolescents everyday experiences, their goals throughout life, expectations for the future and opportunities and risks present in their social contexts. We longed to understand adolescence as a social and psychological phenomenon recognized in much of the world today, but framed within their everyday surroundings and in the specific context of the reality of Comandante Gika neighborhood. We have used a case study analysis based on Bronfenbrenner bioecological theory that takes into account the interaction between the various contexts present in the life of a developing person. Besides Brofenbrenner, the works developed by Santos gave us a model to understand risk and protective factors present in the contexts of adolescents lives exposed to factors of social vulnerability, assessing, as well, the choices made by the subjects. The case studies led us to the following results: family, school, groups of friends, neighborhood relationships, church and work are the most immediate contexts present in the adolescents lives. The insertion into a profession and school learning appear as main key factors in the adolescents plan for the upcoming life, and this plan is related to providing support to the family. The interaction between the family and school contexts seemed important, and the family investment may hinder or facilitate insertion of youths into school. Within the school, the existence of a teacher interested in these teenagers learning and development consisted as a protective factor, facilitating the link between young people and the school. We also noticed, within the boundaries of the research, a lack of public policies that may provide further subsidies to the adolescents development, such as, support for one-parent families and better conditions to be inserted in the labor market. Furthermore, educational policies also proved to be necessary so that the school may ensure access to cultural assets and the learning of school subjects, especially when present in features linked to school failure and dropout.